Sosialisasi etika bermedia sosial pada siswa SMK Muhammadiyah Parung, Kabupaten Bogor - Fajar Adi Prakoso; Zulfikar Ramadhan (University of Muhammadiyah Malang, 2022)
The development of information technology today tends not to be controlled because of situations and conditions requiring conformity with science and technology development. The younger generation needs to be given the education to filter the impact of developing technology, especially the use of social media that contains Negative Content, Hoaxes, and Hate Speech. There are three stages in socializing ethics with social media: the preparation, implementation, and evaluation stages. The results of the socialization of students understand material related to social media ethics, harmful content, hoaxes, and hate speech. At the same time, the social media that are often used are dominated by WhatsApp, Instagram, and Facebook.